Analysis of Factors Affecting Early Childhood Social Development - Musafir, Musafir; Pasigar, Andi; Fatihaturrahmi, Fatihaturrahmi; Erlinawati, Erlinawati; Halimatussakdiah, Halimatussakdiah; Sarmiati, Nopi; Putri, Nurlizawati; Sriwahyuningsih, Sriwahyuningsih; Zakia, Sugitri Ayu; Sulpiyana, Sulpiyana (Jurnal Ilmiah Mandala Education (JIME), 2025)
The purpose of writing this article is to define the introduction of the environment and the influence of the environment on the social aspects of early childhood. The environment can influence social aspects in early childhood. Writing this article uses the literature study method, namely collecting reading sources from previous journals to determine the influence that occurs on children's social aspects in the environment. The results of the analysis and discussion show that what influences children's social aspects is 1) Family environment, 2) School environment, and 3) Community environment. Where when the environment is very good for early childhood it will have a very big influence on the social aspects of early childhood.